Therapeutic reflections on the tennis elbow - Rodineau, J. (2001)
At present, several dozens of treatment methods are available for tennis elbow. These methods can be grouped into two categories: Those that address acute forms of tennis elbow and primarily involve rest, NSAIDs, cooling with ice, exercises for the elbow or wrist and local corticosteroid injections. Those that take chronic forms of tennis elbow into consideration and involve numerous physical treatments, varying from physiotherapy to exercise therapy, osteopathic manipulation of the vertebral column and a large variety of surgical techniques. The physiotherapeutic treatments most often prescribed are ultrasound, iontoferesis, laser therapy, TENS and ultracorporal shock wave therapy. Manual treatments that are frequently prescribed include deep transverse massage by Cyriax, connective tissue therapy, stretching of the muscle-tendon units and also vertebral and articular manipulations. One should never lose sight of the ultimate goal of treatment of tennis elbow, which is to try to stimulate collagen production and promote restoration of normal vascularisation in order to realise healing of the tendon lesion. This is the only guarantee of permanent healing. However, few of the therapeutic protocols in use actually serve this goal. Before undertaking treatment of tennis elbow, therefore, the primary goals of treatment should be memorised: - To eliminate, or at least reduce elbow pain. - To maintain the mobility of the joint, flexibility of the muscular chain and the strength of the fingers and wrist extensors. - To develop the patient's endurance capacity for repetitive and prolonged movements with the forearm muscles. While no studies have shown that NSAIDs improve healing, it cannot be denied that they decrease pain. However, they do not improve grip strength or have any lasting effect on function. Prescribers should never forget that they also have harmful effects on general health. NSAIDs can be used for their analgesic effects, but therapy should never be prolonged more than necessary. Local corticosteroid infiltrations should be used for one reason only: to give relief to patients with severe pain, in order to enable them to follow a rehabilitation program. The medium and long-term effects of local corticosteroid injections are disappointing. In most cases, however, they have a very rapid and positive effect on the alleviation of pain and normalisation of resistance tests of the wrist extensors. This results in a temporary elevation of the percentage of satisfied patients. Unfortunately, after two to three months the beneficial effects of treatment disappear and after six to 12 months, the results are no better than for a placebo. Treatment by corticosteroid infiltration therefore raises many questions (regarding when it should be used in relation to the onset of pain, which product should be used and the appropriate dose), because it does not solve the problem of tennis elbow. Only a specific rehabilitation program, consisting of exercises that improve the quality and resistance of the tendon tissue within the constraints of the sporting activity, can really succeed in healing the lesions. Without such a program, the injury may well become chronic and the lesions may not heal. Surgical treatment should be reserved for patients who do fail to respond well to a carefully designed rehabilitation program with good rehabilitation exercises. Surgery should be aimed at debriding the site of the lesion and revitalising the modified tendon tissue. This dual aim does not seem to be the primary concern of all surgeons, because very often they are content with a simple de-insertion of the tendon. However, one should not merely de-insert the common tendon of the epicondyle, but should also carefully excise all the pathologic tissue and also repair the aponeurosis.